A Novel ECM1 Splice Site Mutation in Lipoid Proteinosis: Case Report plus Review of the Literature - Rey, Linda K. (Mol Syndromol, 2016)
Lipoid proteinosis (LP) is an autosomal recessive genodermatosis known to be caused by mutations in ECM1. Nonsense and missense mutations are the most common variations in LP. Up to date, only 6 splice site mutations have been observed. We report on a 26-year-old female LP patient from a Turkish consanguineous family carrying a novel homozygous splice site mutation in intron 8 of the ECM1 gene and summarize the current knowledge on ECM1 mutations and possible genotype-phenotype correlations.